1997
DOI: 10.1002/anie.199720121
|View full text |Cite
|
Sign up to set email alerts
|

NADH‐Dependent Halogenases Are More Likely To Be Involved in Halometaolite Biosynthesis Than Haloperoxidases

Abstract: The detection of chloroperoxidase from the fungus Caldariomycesfumagofll and the development of a simple spectrophotometric assay12] for the detection of halogenating enzymes based on the synthetic compound monochlorodimedone (1) as organic substrate resulted in the subsequent isolation of a number of haloperoxidases from different organisms. All H3C CH3these enzymes produce hypohalogenic acid, which is the actual halogenating agent. Thus, halogenation catalyzed by haloperoxidases lacks substrate and regiospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
74
0
4

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(80 citation statements)
references
References 12 publications
2
74
0
4
Order By: Relevance
“…In FAD-dependent hydroxylations the flavin is reduced by NAD(P)H and reacts with oxygen to form the 4(a)-flavin hydroperoxide; the hydroperoxide oxidizes the substrate to an epoxide, which is then opened by nucleophilic attack from a hydroxyl ion (Entsch et al, 1976;Gatti et al, 1994). A similar mechanism proposed for halogenasecatalysed reactions (Hohaus et al, 1997;Keller et al, 2000) is supported by recent evidence (van Pée, 2001) that the halogenase gene product requires FAD, NADPH, reductase activity and oxygen to function as a halogenating system. The epoxide generated by the flavin hydroperoxide undergoes nucleophilic attack by a halide ion, and specific removal of water gives the halogenated product.…”
Section: Function Of Cmlsmentioning
confidence: 95%
See 1 more Smart Citation
“…In FAD-dependent hydroxylations the flavin is reduced by NAD(P)H and reacts with oxygen to form the 4(a)-flavin hydroperoxide; the hydroperoxide oxidizes the substrate to an epoxide, which is then opened by nucleophilic attack from a hydroxyl ion (Entsch et al, 1976;Gatti et al, 1994). A similar mechanism proposed for halogenasecatalysed reactions (Hohaus et al, 1997;Keller et al, 2000) is supported by recent evidence (van Pée, 2001) that the halogenase gene product requires FAD, NADPH, reductase activity and oxygen to function as a halogenating system. The epoxide generated by the flavin hydroperoxide undergoes nucleophilic attack by a halide ion, and specific removal of water gives the halogenated product.…”
Section: Function Of Cmlsmentioning
confidence: 95%
“…Nevertheless, experiments with isotopically labelled potential precursors such as acetate, malonate and acetoacetate (Simonsen et al, 1978;Groß et al, 2002) have not firmly identified the substrate that, upon chlorination, provides the activated dichloroacetyl intermediate. Recently new avenues for exploring the mechanisms that introduce halogens into natural products have been opened by the discovery of FADH 2 -dependent halogenases (van Pée, 2001), and by demonstrations of their role in the biosynthesis of halogenated secondary metabolites (Hohaus et al, 1997;Kirner et al, 1998;NowakThompson et al, 1999;Keller et al, 2000;Puk et al, 2002). Halogenase genes have now been cloned from a variety of organisms: e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic manipulation in P. fluorescens BL915 has identified the intermediate products from each enzyme in the pyrrolnitrin pathway, leading to the current model for the biosynthetic pathway (4). The first enzyme, PrnA (tryptophan 7-halogenase), incorporates the chlorine into the substrate tryptophan (6). Structural and biochemical analyses of both tryptophan 7 and 5-halogenase (7)(8)(9)(10) have established a novel chemical mechanism of hypohalous acid formation at the flavin cofactor, followed by N-chlorolysine formation (9) and finally regioselective halogenation of tryptophan (controlled by orientation of substrate) (10,11).…”
mentioning
confidence: 99%
“…Molecular genetic studies (9) identified the chl gene as being responsible for the chlorination of tetracycline in Streptomyces aureofaciens. Biochemical studies showed that a FADH 2 -dependent halogenase (PrnA) is involved in the biosynthesis of the tryptophan-derived halometabolite pyrrolnitrin in Pseudomonas fluorescens (20,27). Biosynthetic studies of NCZs could allow us to characterize a novel type of PKS for the polyenone skeleton and an as yet unknown halogenase involved in the biosynthesis of an aliphatic halometabolite.…”
mentioning
confidence: 99%